Scaling Up Breastfeeding in Myanmar through the Becoming Breastfeeding Friendly Initiative. Issue 8 (12th July 2019) - Than, May Khin; Nyi, Soe Nyi; Hlaing, Lwin Mar; Mar, Swe Le; Thwin, Theingi; Cashin, Jennifer; Pérez-Escamilla, Rafael; Harding, Kassandra L
ABSTRACT: Background: Optimal breastfeeding practices in Myanmar are above global averages, and the Ministry of Health and Sports (MoHS) has demonstrated its commitment to support nutrition and breastfeeding through continued policy and program actions. In 2017, the MoHS, in partnership with Save the Children, led the piloting of the Becoming Breastfeeding Friendly (BBF) Initiative. BBF provides a guide for countries to assess the enabling environment for breastfeeding and a country's readiness to scale up breastfeeding policies and programs. Objective: The aim of this study was to document the BBF process and outcomes in Myanmar. Methods: A Working Group (WG) of 14 members, led by a chair and 2 cochairs, conducted the BBF assessment using the BBF Index (BBFI), generated and prioritized recommendations, and disseminated the findings over the course of 5 meetings. Additional meetings were held to gain stakeholder endorsement and approval of the BBF process and WG before commencement and MoHS endorsement of the findings. Results: The BBFI score for Myanmar was 1.2 out of 3.0, which indicates a moderate environment for scaling up breastfeeding policies and programs. The Funding and Resources gear earned the lowest score (0.5), whereas Political Will earned the highest score (2.0). Overall, 4 gears were weak and 4 were moderate in strength. Nine recommendation themes were generated and prioritized. The top priority recommendation was to form a National Infant and Young Child Feeding Alliance. The MoHS endorsed the 9 recommendations in December 2018 and has provided leadership for the formation of the alliance. Conclusions: The BBF Initiative was successfully conducted in Myanmar, resulting in 9 prioritized recommendations for strengthening the breastfeeding enabling environment and substantial interagency collaborations. Adaptations to the BBF process were made for the context, and we note numerous lessons learned that should be considered by other countries that plan to commit to the BBF Initiative.